The Role of Lies in the Sociocultural Life of Spanish-Speaking Peoples - Tursunova, Parvina (The Lingua Spectrum, 2025)
This article examines the phenomenon of lies in the sociocultural life of Spanish-speaking peoples, analyzing the functional role of lies in social, cultural, and political contexts. The research is based on anthropological, sociolinguistic, and cultural studies approaches. It also explores the social status of lies, their cultural foundations, and literary expressions in the context of Latin America and Spain.